An Upper Take on Doubler-Uppers - Alexandra Bagasheva (Languages, 2024)
Against the background of comparatively insufficient, expressly dedicated studies on double particle verb person nominalisations, this paper offers a qualitative, cognitive-constructionist approach to the properties of doubler-upper nominalisations of particle verbs in English and a reappraisal of some of the available analyses thereof. On the assumption of the validity of the flexicon stance on the organisation of words in the human mind, and on the basis of a preliminary semantic analysis of 300 types of doubler-upper nouns extracted from two corpora and Urban Dictionary, it is claimed that there are no identifiable constraints on the possibility of double-er marking and no particular properties of particle verbs as bases to preclude double -er marking. A hypothesis is formulated that, despite their deviance, doubler-uppers strike the optimal balance between complexity and unity and appear to be the most natural and morphophonologically best-fitting pattern for particle verb -er nominalisation (at least in spoken discourse and the media).